Design of Novel Aminoglycoside Derivatives with Enhanced Suppression of Diseases-Causing Nonsense Mutations - Sabbavarapu, Narayana Murthy (ACS Med Chem Lett, 2016)
[Image: see text] New pseudotrisaccharide derivatives of aminoglycosides that exploit additional interaction on the shallow groove face of the decoding-site rRNA of eukaryotic ribosome were designed, synthesized and biologically evaluated. Novel lead structures (6 and 7 with an additional 7′-OH), exhibiting enhanced specificity to eukaryotic cytoplasmic ribosome, and superior nonsense mutation suppression activity than those of gentamicin, were discovered. The comparative benefit of new leads was demonstrated in four different nonsense DNA-constructs underling the genetic diseases cystic fibrosis, Usher syndrome, and Hurler syndrome.